The Effect of Nutritional Interventions to Improve the Nutritional Status of Cancer Patients Undergoing Chemotherapy - Wahyuningsih, Rita Sri; Allenidekania, Allenidekania (GLOBAL HEALTH SCIENCE GROUP, 2024)
Cancer is a catabolic inflammatory disease that causes patients to experience frequent weight loss, or even cachexia in severe cases. Malnutrition in cancer patients impairs quality of life and therapeutic response, further leading to a poor prognosis. This study aims to determine various types of nutritional interventions that can improve the nutritional status of cancer patients undergoing chemotherapy. The research method used is a systematic review through electronic databases and websites, namely PubMed, Scopus, ProQuest, and MedLine. The keywords used for the search were